The tadpole of Dendropsophus haddadi (Bastos & Pombal 1996) (Hylidae: Hylinae) - Lourenço-De-Moraes, Ricardo; Campos, Felipe Siqueira; Toledo, Luís Felipe (Zootaxa, 2012)
The genus Dendropsophus Fitzinger, 1843 currently includes 92 species of hylid treefrogs distributed from South and Central America to southern Mexico (Frost 2011). Dendropsophus haddadi is a small species of this genus (male SVL 15–19 mm; female SVL 21–24 mm) that is allocated in the D. decipiens clade, part of the D. microcephalus group, together with other three species: D. berthalutzae, D. decipiens, and D. oliveirai (Faivovich et al. 2005; Frost 2011). This species was recorded in regions of ombrophilous Atlantic forest and scrubby restinga vegetation mainly in coastal areas between the state of Espírito Santo and Pernambuco, Brazil (Bastos & Pombal 1996; Amorim et al. 2009; Camurugi et al. 2010; Araújo-Neto et al. 2012), ranging from sea level up to 650 m of elevation (Peixoto & Pimenta 2004). In this paper, we described the tadpole of D. haddadi from a population from southern Bahia, northeastern Brazil.